Polymer Engineering Science and Viscoelasticity: an introduction - Brinson, H. F. (Springer, 2017)
A mechanics perspective on the mathematics of viscoelasticity and a materials view of the physical mechanisms behind the polymer deformation processes, are provided by this book. The book fills a critical niche. Clearly written and well-organized, the volume includes an introduction to and mathematical description of the basic materials science of polymers, time-temperature-frequency dependence, and unique deformation mechanisms of polymers.